The differences in heat stress resistance due to dairy cattle breed - Vesna Gantner; Tina Bobić; Maja Gregić; Ranko Gantner; Krešimir Kuterovac; Klemen Potočnik (Mljekarstvo)
Considering the rapid climate changes worldwide, with the purpose to reduce financial losses for dairy farmers and enable a more sustainable farming as well, there is an increasing necessity to implement breeding values for heat resistance in breeding strategies. The estimation of breeding values requires a determination of temperature-humidity index (THI) threshold value. Therefore, the objective of this study was to determine the temperature-humidity index (THI) threshold values for daily milk yield, daily fat and protein content of milk produced by Holsteins and dairy Simmentals in Croatian farms. With that purpose, 1.070,554 test-day records from 70.135 Holsteins reared on 5.679 farms and 1.300,683 test-day records from 86.013 Simmentals reared on 8.827 farms in Croatia were compared to records of ambient temperature and relative humidity collected in the barn, during regular milking recordings from January 2005 to December 2012. Accordingly the following conclusions could be drawn: threshold values for daily milk yield were highly dependant on the parity and breed (Holsteins: 68, 69 and 72 for 1st, 2nd, 3+ parity; Simmentals: 77 for 1st); daily fat and protein contents showed a highly significant decrease due to heat stress condition (THI in 66-80) in both, Holstein and Simmental cows, and in all parity classes; multiparous cows were more resistant to heat stress than primiparous; Simmental cows were more resistant to heat stress than Holsteins.